Identification and Characterization of Viral and Bacterial Pathogens in Free-Living Bats of Kopaonik National Park, Serbia - Dejan Vidanović; Nikola Vasković; Marko Dmitrić; Bojana Tešović; Mihailo Debeljak; Milovan Stojanović; Ivana Budinski (Veterinary Sciences)
This pilot study investigated the presence of potentially zoonotic microorganisms in bat species from Kopaonik National Park, Serbia. A total of 40 individuals from 12 bat species were sampled and screened using microbiological and molecular methods. Salmonella spp., Chlamydia spp., Coxiella burnetii, Francisella tularensis, Leptospira spp., Lyssavirus, Filoviridae, henipaviruses, and SARS-CoV-2 were not detected in any bats. Coronavirus genomes were confirmed in four bats—one Myotis brandtii, two Myotis daubentonii, and one Myotis cf. mystacinus. Sequence analysis identified the presence of alphacoronavirus genomes with high similarity to strains previously found in Europe. Mycoplasma spp. genomes were found in 18 bats (45%), and Rickettsia spp. were detected in five bats (12.5%), although species-level identification was not possible. The findings highlight the presence of certain bacteria and viruses in bats that could have implications for public health, especially in areas with close human–wildlife interaction. Although no direct evidence of high-risk pathogens was found, the results support the importance of continued surveillance and ecological studies on bats, given their role as potential reservoirs. Monitoring bat-associated microorganisms is essential to better understand possible transmission routes and improve the prevention of emerging zoonotic diseases.